MECHANISMS FOR MODERNIZATION, SOCIALIZATION AND INTEGRATION OF ENVIRONMENTAL EDUCATION IN THE CONDITIONS OF ECOLOGICAL GLOBALIZATION - Sodiqov Jaxongir Toshpulat o’g’li (American Journals, 2026)
This article analyzes the relevance of environmental education in the context of ecological globalization, the mechanisms for its adaptation to national state science programs, as well as the ways of modernization, socialization and integration. The article studies the current state of environmental education, its problems, their causes and consequences on a scientific basis. Proposals are developed to increase the role of environmental education in combating global environmental problems (climate change, loss of biodiversity, resource scarcity). The article highlights the areas of integration of environmental education into national science programs in our country, the use of innovative technologies, active involvement of society and taking into account international experience.
Keywords: Environmental education, ecological globalization, modernization, socialization, integration, national science programs, mechanisms.